2013
DOI: 10.1128/aem.03575-12
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Dermacentor silvarum Olenev (Acari: Ixodidae) by Coxiella-Like, Arsenophonus-Like, and Rickettsia-Like Symbionts

Abstract: We report that multiple symbionts coexist in Dermacentor silvarum. Based on 16S rRNA gene sequence analyses, we prove that Coxiella-like and Arsenophonus-like symbionts, with 95.6% and 96.7% sequence similarity to symbionts in the closest taxon, respectively, are novel. Moreover, we also provide evidence that the Coxiella-like symbiont appears to be the primary symbiont.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…The results are consistent with reports identifying Coxiella -like bacteria or endosymbionts in a number of Haemaphysalis , Dermacentor , and Amblyomma tick species (Lee et al 2004, Jasinskas et al 2007, Klyachko et al 2007, Liu et al 2013, Arthan et al 2015, Duron et al 2015). Several female ticks of Haemaphysalis and Amblyomma sampled here were fully engorged, hence it is possible that any Coxiella DNA observed may have originated from host blood.…”
Section: Discussionsupporting
confidence: 90%
“…The results are consistent with reports identifying Coxiella -like bacteria or endosymbionts in a number of Haemaphysalis , Dermacentor , and Amblyomma tick species (Lee et al 2004, Jasinskas et al 2007, Klyachko et al 2007, Liu et al 2013, Arthan et al 2015, Duron et al 2015). Several female ticks of Haemaphysalis and Amblyomma sampled here were fully engorged, hence it is possible that any Coxiella DNA observed may have originated from host blood.…”
Section: Discussionsupporting
confidence: 90%
“…These results have indicated that these bacteria are considered as predominant bacteria in ticks in China, consistent with previous studies (Gao et al 2010;Liu et al 2013;Sun et al 2015). The present and previous results (Moreno et al 2006;Tveten and Sjåstad, 2011;Xu et al 2015) have demonstrated that bacterial diversity differed significantly in different tick species.…”
Section: Discussionsupporting
confidence: 94%
“…Rickettsia bacteria shared the highest sequence similarity (99.8%) with symbiotic Rickettsia of D. varibilis (GenBank: U55820) [54]. In males, the second abundant microbes (designated as ALS-Hl) belonged to Arsenophonus , sharing over 99.5% and 97.9% similarity to symbionts of D. silvarum (GenBank: JN866582) [55] and D. variabilis (GenBank: AY265342) [56], respectively . Following ALS-Hl, there were RLS-Hl and NCLS-Hl.…”
Section: Resultsmentioning
confidence: 99%
“…It is now widely accepted that the co-infection with multiple symbionts occurs in many arthropod hosts [60]. However, co-infection with symbionts has been demonstrated only in a few tick species, such as A. americanum [5], Ornithodoros moubata [61], D. silvarum [55] and Rh. sanguineus [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation